Academic labour, journal ranking lists and the politics of knowledge production in marketing. Issue 1 (2nd January 2016) - Tadajewski, Mark
ABSTRACT: In this paper, we engage with the rising importance of journal ranking lists. We explore the pressure these place on marketing academics and the politics of knowledge production, stressing academic game-playing, careerism, and paradigmatic homogeneity. We appreciate that scholars are disciplined by these lists, their line managers, and reaffirm list power through their own patterns of self-management. Nonetheless, marketing academics should avoid making the naïve assumption that the appearance of a paper in a highly rated journal necessarily serves as a proxy for 'quality'. Publication in a particular outlet does not transform the ultimate contribution being made in any substantive fashion. We provide an extensive critique of the function and impact of journal lists. However, it is also recognised that these are very important for members of the marketing community. As such, we explain our reasons for contesting the recent regrading of the Journal of Marketing Management ( JMM ) by a prominent journal list and underline the changes that have been made to the Journal since the beginning of the current editorial term. Finally, the support of prominent scholars among our thought community for the policies being implemented is highlighted and we underscore the rigour of contributions to the Journal, the review process, the rising citations, downloads and truly global readership of the JMM .